Main factors of success of leader behavior: review of theoretical approaches (Actual Problems of Psychology in Educational Institutions, 2022)
The article considers selected concepts of leadership behavior. The features of the leader are presented, among which there are two main ones that determine the effectiveness of leadership: the ability to make decisions in a situation of uncertainty, heightened risk, high level of complexity and the leader's responsibility for the decisions made.